Association of variants in the fat mass and obesity associated (FTO) gene with polycystic ovary syndrome. - Barber, T; Bennett, A; Groves, C; Sovio, U; Ruokonen, A; Martikainen, H; Pouta, A; Hartikainen, A; Elliott, P; Lindgren, C; Freathy, R; Koch, K; et al. (2008)
AIMS/HYPOTHESIS: Variants in the fat-mass and obesity-associated gene (FTO) influence susceptibility to type 2 diabetes via an effect on adiposity/obesity. Given the important role of obesity in the aetiology of both polycystic ovary syndrome (PCOS) and type 2 diabetes mellitus, our aim was to establish whether FTO variants are also implicated in PCOS susceptibility. METHODS: We performed a genetic association study of FTO variant rs9939609 using case-control analyses, conducted in 463 PCOS patients (geometric mean BMI 27.5 kg/m(2)) and 1,336 female controls (geometric mean BMI 25.3 kg/m(2)) of UK British/Irish origin. We also sought evidence for associations between FTO variation and circulating testosterone levels in 324 UK PCOS patients and 1,000 women from the Northern Finland Birth Cohort of 1966. Outcome measures included FTO rs9939609 genotype frequencies by participant group and androgen measures (testosterone, free androgen index) by genotype. RESULTS: There was a significant association between FTO genotype and PCOS status in the UK case-control analysis, which was attenuated by adjustment for BMI (Cochran-Armitage test, odds ratio [per minor allele copy] 1.30 [95% CI 1.12, 1.51], p = 7.2 x 10(-4) [unadjusted], p = 2.9 x 10(-3) [adjusted]). This association was most evident in obese PCOS patients (PCOS patients below median BMI vs UK controls, p = 0.11; above median BMI vs controls, p = 2.9 x 10(-4)). No relationship between FTO genotype and androgen levels was seen. CONCLUSIONS/INTERPRETATION: We provide the first evidence that variants that predispose to common obesity also result in altered susceptibility to PCOS, confirming the mechanistic link between these conditions. The predominant effect of FTO variants on PCOS susceptibility is probably mediated through adiposity.